A new micropterous, ground‐dwelling, non‐cyclostome braconid parasitoid wasp, Epigeiobracon perplexus Quicke & Ward, gen. et sp. nov. (Hymenoptera: Braconidae) from New Zealand of uncertain relationships. Issue 3 (29th August 2019) - Quicke, Donald L J; Ward, Darren F; Butcher, Buntika A
Abstract: A morphologically highly derived, litter‐dwelling, apterous, non‐cyclostome braconid wasp from New Zealand is described and illustrated as Epigeiobracon perplexus Quicke & Ward, gen. et sp. nov. The subfamilial placement of the new taxon based on morphology seems impossible though a protruding face, well‐developed round pronope and presence of a few apical pegs on the hind tibia are suggestive of Orgilinae, but we cannot completely rule out the small subfamily Microtypinae with which the new genus shares an extremely reduced third segment of the labial palp.